Zasady opracowania studium wykonalności - Zbroja, Andrzej (The Rules of Developing Feasibility Studies, 2006)
In article the rules of feasibility study elaboration in agreement with requirements stood to all projects which are realized within the limits of Operational Programm Regional Development, financed by European Regional Development Fund (ERDF). The main accent laid on compactness of each part of feasibility study together with their readable.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 263-273